A study on vitamin D level among the patients attending in a private chamber in Dhaka city - Eva, Moushumi Afrin; Begum, Nasreen; Kabir, ASM Anawrul; Ahmed, Khondoker Wasee; Sharmin, Mahbuba; Saha, Sumanta Kumar; Bayazid, Md Bodroddoza; Hasan, Shahriar (Northern International Medical College Journal, 2020)
Background: Vitamin D deficiency is one of the most neglected public health issues all over the world. Near about 1 billion people round the world suffer from vitamin D deficiency. Most of the countries in Asia having high prevalence of vitamin D deficiency. Objective: To find the vitamin D level among the patients attending in a private chamber in Dhaka city Methodology: A cross sectional observation study was carried out in a renowned diagnostic center of Dhaka city from July 2017 to June 2018. A sample of 1523 adult patients aged 18 years and above, presented with generalized body aches and pains selected conveniently for the study. Blood samples were taken and serum vitamin D levels were measured. In this study, vitamin D concentration below10 ng/ml was considered as vitamin D deficiency, 20–30 ng/ml as insufficiency, and 30–100 ng/ml as vitamin D sufficient. Data were analyzed by using SPSS version 22. Result: Out of 1523 patients 69.5% were women and 30.5% men. Urban and rural distribution was 63.16% and 36.84% respectively. Among the participants vitamin D deficiency was 54%, 35.8% vitamin D insufficient, and only 9.8% had normal level of vitamin D, regarding age specific deficiency highest 71.8% was in 71-80 years age group. Out of 1058 female 39.5% were vitamin D deficient, 45.6% had insufficient vitamin D level. Only 14.9% female were found normal level. Age specific deficiency found highest 63.8% in 61-70 year age group. On the other hand out of 465 male participants, 24% were vitamin D deficient, 34% were insufficient and 42% had normal level vitamin D. Highest deficiency 42.5% found in age group 61-70years. Conclusion: Considering the study result deficiency was higher among female than male. In female vitamin D deficiency increased after age of 31year. Vitamin D deficiency found highest in old age and middle age group. Over all age specific deficiency found significantly highest in 71 – 80 years. In both male and female Vitamin D deficiency was found highest above 61years of age. Northern International Medical College Journal Vol.10 (2) Jan 2019: 393-396